Indigenous Processes of Consent: Repoliticizing Water Governance through Legal Pluralism - Curran, Deborah (Water, 2019)
While international instruments and a few state governments endorse the “free, prior and informed consent” of Indigenous peoples in decision-making about the water in their traditional territories, most state water governance regimes do not recognize Indigenous water rights and responsibilities. Applying a political ecology lens to the settler colonialism of water governance exposes the continued depoliticizing personality of natural resources decision-making and reveals water as an abstract, static resource in law and governance processes. Most plainly, these decision-making processes inadequately consider environmental flows or cumulative effects and are at odds with both Indigenous governance and social-ecological approaches to watershed management. Using the example of groundwater licensing in British Columbia, Canada as reinforcing colonialism in water governance, this article examines how First Nations are asserting Indigenous rights in response to natural resource decision-making. Both within and outside of colonial governance processes they are establishing administrative and governance structures that express their water laws and jurisdiction. These structures include the Syilx, Nadleh Wut’en and Stellat’en creating standards for water, the Tsleil-Waututh and Stk’emlúpsemc te Secwépemc community assessments of proposed pipeline and mining facilities, and the First Nations of the Nicola Valley planning process based on their own legal traditions. Where provincial and federal environmental governance has failed, Indigenous communities are repoliticizing colonial decision-making processes to shift jurisdiction towards Indigenous processes that institutionalize responsibilities for and relationships with water. This research was funded by the Social Sciences and Humanities Research Council grant number 890-2015-0115 and the Real Estate Foundation of British Columbia grant number 2016-11. Faculty Reviewed